Ecoliteracy Representation in Life Today English Textbook: A Content Analysis - Raisha Puteri Kamila Sukma; Imam Santosa (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
Environmental problems require school curricula to develop learners who understand ecological issues and act responsibly toward the environment. English textbooks are important because they teach language while also transmitting ecological meanings through texts, images, dialogues, and tasks. This study analyzed how ecoliteracy is represented in the Grade XII English textbook Life Today. Using qualitative content analysis and Roth's ecoliteracy framework, the study coded textual, visual, and instructional units into four aspects: knowledge, skills, affect, and behavior. The analysis identified 214 ecoliteracy-related segments. Knowledge was dominant with 119 occurrences, followed by skills with 44, affect with 28, and behavior with 23. The findings show that the textbook integrates environmental and sustainability themes, but the representation is cognitively dominant and less balanced in developing affective engagement and concrete environmental action. Future English textbooks should include more project-based, reflective, and community-oriented tasks to strengthen holistic ecoliteracy.